Organizational Change and Managerial Sensemaking: Working Through Paradox - LÜScher, Lotte S.; Lewis, Marianne W. (Academy of Management Journal, 2008)
As change becomes a constant in organizational life, middle managers charged with interpreting, communicating, and implementing change often struggle for meaning. To explore change and managerial sensemaking, we conducted action research at the Danish Lego Company. Although largely absent from mainstream journals, action research offers exceptional access to and support of organizational sensemaking. Through collaborative intervention and reflection, we sought to help managers make sense of issues surfaced by a major restructuring. Results transform paradox from a label to a lens, contributing a process for working through paradox and explicating three organizational change aspects–paradoxes of performing, belonging, and organizing.